Graciliano, ele mesmo e os outros: Uma voz que grita, denuncia e captura as durezas da vida - Silva, Danielle Mansur Lima (2024)
This research aims to analyze Infância, a novel by Graciliano Ramos through autobiographical studies such as the theorist Phillipe Lejeune, the power relations with Foucault, studies on memory in social sciences area by Maurice Halbwachs. Since these theorists and others, we will bring to the fore the family relations, power relation and subjectivation themes, as well as social and religious issues, noting that this is a patriarchal context in which the narrative is inserted.